Treatment Intervention Programmes For Autism - maouche, abdelhamid; makhloufi, ali (Journal of Social Sciences and Humanities, 2024)
Autistic children cannot study in (regular) general education programs without modifications in the curriculum, methods, or teaching methods, or taking into account the individual’s disability circumstances. That is, they need adapted programs that help them learn in order to guarantee this group equal opportunities in learning like other normal people. The concept of therapeutic intervention is considered one of the concepts that is of interest to all workers and those interested in the field of caring for people with special needs, and treating autism is one of the most controversial issues in the educational community in recent years, as societies that still strive to care for the disabled and rehabilitate them and look to their education As a primary goal, because statistics have shown the presence of large numbers of autistic people, these data require concerted efforts to integrate autistic groups academically, educationally, psychologically, and socially, and to prepare appropriate treatment programs for them to provide the best possible care for them.